Household perceptions of healthy broiler meat and their impacts on purchasing practices in the Greater Jakarta Area, Indonesia - Ening Ariningsih; Sumaryanto Sumaryanto; Mewa Ariani; Nyak Ilham; Eni Siti Rohaeni; Adang Agustian; Sri Hastuti Suhartini; Achsanah Hidayatina; Suharyon Suharyon; Dwi Priyanto; Dedi Sugandi; Thomas Agoes Soetiarso; et al. (Cogent Food & Agriculture)
This study examines how household perceptions of healthy broiler meat influence purchasing behavior in the Greater Jakarta Area. We surveyed 521 households using a multistage random sampling. Data analysis employed Multiple Indicators Multiple Causes models and ordered probit regression. Our key findings reveal that the majority of households fall within the medium perception category of healthy broiler meat. Purchasing practices align with perceptions, with households prioritizing healthier options when they perceive them as such. Furthermore, higher-income households are more likely to purchase healthier broiler meat. The dominance of wives in broiler meat purchase decisions suggests targeting women with educational initiatives that promote healthy food choices. This study highlights the importance of understanding household perceptions and purchasing practices toward healthy broiler meat, which can help support the development of healthy food products.